Introduction to web application security testing with Kali Linux. (O'Reilly Media, Inc., 2018)
Most businesses today use web applications to interact with their customers. These web applications can provide hackers with the entry points they use to attack internal business systems, allowing the possibility of data theft or corruption. This video, designed for entry to intermediate-level security engineers, describes the vulnerabilities often found in web apps, shows you the techniques hackers typically use to exploit those vulnerabilities, and explains the processes and toolsets you can use to test for and remediate against those vulnerabilities. Participants should have access to Kali Linux before starting the course. Understand how to identify web-based vulnerabilities and remediate against them Explore hacker techniques like cross site scripting, SQL injection, and command injection Learn how to identify web app misconfigurations and how to correct them Survey web app vulnerability analysis tools like HackBar, XSS Rays, and PageXray Discover techniques and toolsets (SSLScanner, Google Hacking, etc.) that test for vulnerabilities Ric Messier (GCIH, GSEC, CEH, CISSP) is the Director for Cyber Academic Programs at Circadence. He has decades of information security experience and is the author of dozens of O'Reilly titles on infosec and digital forensics, including Introduction to Penetration Testing and Learning Linux Security. He holds a BS in Information Technology from the University of Massachusetts, an MS in Digital Forensic Science from Champlain College, and a PhD in Information Assurance and Security from Capella University.